Please See Us - Mullen, Caitlin (New York : Pocket Books, 2020)
Summer has come to Atlantic City but the boardwalk is empty of tourists, the casino lights have dimmed, and two Jane Does are laid out in the marshland behind the Sunset Motel, just west of town. Only one person even knows theyre there. Meanwhile, Clara, a young boardwalk psychic, struggles to attract clients for the tarot readings that pay her rent. When she begins to experience very real and disturbing visions, she suspects they could be related to the recent cases of women gone missing in town. When Clara meets Lily, an ex-Soho art gallery girl who is working at a desolate casino spa and reeling from a personal tragedy, she thinks Lily may be able to help her. But Lily has her own demons to face. If they can put the pieces together in time, they may save another lost girl--so long as their efforts dont attract perilous attention first. Can they break the ill-fated cycle, or will they join the other victims?
Keywords: Female friendship -- Fiction; Women psychics -- Fiction; Single women -- Fiction; Missing persons -- Fiction; Women -- Crimes against; Fiction; Atlantic City (N.J.) -- Fiction; Thrillers (Fiction); Detective and mystery fiction